Methodological slip for the figurative of graphical folds narratives: between network analysis and discursive conjunctions - Belalcazar Valencia, John Gregory (AWARI, 2020)
The ARS is not, nor does it turn out to be defined, to "fix" the graphical representation of a relational situation, since, in the condition of apprehending the "relational situations" to present and represent from a graph, the problem of recognizing alternative explanations begins, given the broad interpretative horizon of talking about social relations, in view of the type of actors-agents that are observed, given the types of networks that are deployed, given the traces that are "drawn" in a clear reference to their engines, its extensions, its links and connections, its externalities that unfold in its event. The interesting thing here in the pretensions of the discussion that comes throughout the document is to enter a system with the analysis systems and the coding with its reading under its graphics language that brings the Analysis of Social Networks -ARS-, to enter in a much more qualitative perspective of a narrative nature. A reflection arises on the conditions and situations of information collection, on the nature of the data and its contextualization, on interpretation, trying to examine here the support that qualitative analysis techniques such as "Conversational Analysis" and "Discursive Practices" can provide. We can also recognize the narratives and with them their stories and their versions available to the ARS, an analytical resource based on visualizing a network of relationships and transactions, oriented to the production of graphical narrative folds.